diff --git a/documents/by-course/math-8/pset-3/main.typ b/documents/by-course/math-8/pset-3/main.typ index c810b99..bb4dc51 100644 --- a/documents/by-course/math-8/pset-3/main.typ +++ b/documents/by-course/math-8/pset-3/main.typ @@ -276,3 +276,350 @@ The right to left direction is very easy in this case. By directly plugging in $ ] *12a.* + +F. This is a proof that $not A => B$ is a contradiction, which is not +sufficient to show $A => B$. + += 1.6 + +*1b.* + +#proof[ + Consider $m = 1$, $n = -1$. Then $15(1) + 12(-1) = 3$. +] + +*1c.* + +Rewrite $2m + 4n = 7$ as $2(m + 2n) = 7$. Notice that $2(m + 2n) = 2k, exists k +in nonzero$ and therefore is an even number for any $m$, $n$. But 7 is not +even. So no choices of $m$ and $n$ can create a number equal to 7. So no $m$ or +$n$ exists. + +*4a.* + +#proof[ + Consider $x = 2$. Then $x^2 + x + 41 = 46$, which is not prime. So it's false. +] + +*4b.* + +#proof[ + For any $x$, choose $y = -1 dot x$. Then $x + (-x) = x(1 - 1) = 0x = 0$. This + is also trivially true when considering our usual field of reals because the + existence of $y$ such that $x + y = 0$ is an axiom. +] + +*4c.* + +Consider $x = 2$ and $y = 1$. Then $1 > 2$ is false. + +*4d.* + +Consider $a = 10$, $b = 2$, $c = 5$. Then $a | b c$ because $10 | 2 dot 5$ but +10 does not divide either 2 or 5. + +*6a.* + +#proof[ + Rewriting the inequality, + $ + 1 / n <= 1\ + 1 <= n + $ + This is true for all $n in NN$ by the definition of $NN$. +] + +*6b.* + +#proof[ + Rewriting, + $ + 1 / n < 0.13 \ + 1 < 0.13n \ + n > 1 / 0.13 + $ + So such an $M$ is $1/0.13$, because all naturals greater than $1/0.13$ are + greater than $1/0.13$. +] + +*6e.* + +#proof[ + $ + forall n in NN, n + 1 > n + $ +] + +*6f.* + +$ + forall k in ZZ, m = -k, k + m = 0 \ + forall n in NN, 0 <= 0 < n +$ + +*6i.* + +First consider $K = 10$, and therefore + +$ + forall r > 10, r^2 > 100 +$ +Then note that our inequality is equivalent to $r^2 > 100$, which is true for +all $r$. +$ + 1 / (r^2) < 0.01 \ + r^2 > 100 \ +$ +So a $K$ exists, namely $K = 10$. + +*6k.* + +Consider $M = 51$. Then $forall r > 51, 2r > 102$ and $2r > 100$ is always +true. + +$ + 1 / (2r) < 0.01 \ + 2r > 100 +$ + +So such an $M$ exists, namely, $M = 51$. + += 2.1 + +*4a.* + +False. + +*4b.* + +True. + +*4c.* + +False. + +*4d.* + +True. + +*4e.* + +True. + +*4f.* + +False. + +*4g.* + +True. + +*4h.* + +False. + +*4i.* + +False. + +*4j*. + +True. + +*5a.* + +True. + +*5b.* + +True. + +*5c.* + +True. + +*5d.* + +True. + +*5e.* + +False. + +*5f.* + +True. + +*5g.* + +True. + +*5h.* + +True. + +*5i.* + +False. + +*5j.* + +True. + +*5k.* + +True. + +*5L.* + +True. + +*6a.* + +$ + A = {1,2}, B = {1,2,3}, C = {1,2,4} +$ + +*6b.* + +$ + A = B = C +$ + +A particular example might be $A = {1}, B = {1}, C = {1}$. + +*6c.* + +$ + A = {1}, B = {1,2}, C = {3} +$ + +*6d.* + +$ + A = {1,2}, B = {1,2,3}, C = {5,6,7} +$ + +*8.* + +Theorem 2.1.1: $forall A, B, C, A subset.eq B and B subset.eq C => A subset.eq C$. + +#proof[ + $ + forall a in A, a in B \ + forall a in A, exists b in B, a = b \ + forall b in B, b in C \ + forall a in A, a in C => A subset.eq C + $ +] + +*11a.* + +#proof[ + $ + {x in RR : 3 / 4 x - 2 > 10} \ + = {x in RR : x > 16 } \ + = (16, infinity) + $ +] + +*11b.* + +#proof[ + $ + {x in RR : |x - 4| = 2|x| - 2} \ + = {x in RR : |x - 4| = 2|x| - 2} \ + $ + + Now we consider various cases. Consider $x >= 4$. Then + $ + {x in RR : x - 4 = 2x - 2} \ + = {x in RR : x - 4 = 2x - 2} \ + = {x in RR : x = -2} \ + $ + But in this case $x >= 4$. Since there is no $x >= 4$ such that $x = -2$, + this is actually $emptyset$. + + Now consider $0 <= x < 4$. + $ + {x in RR : 4 - x = 2x - 2} \ + = {x in RR : x = 2} \ + = {2} + $ + + + Now consider $x < 0$. Then + $ + {x in RR : 4 - x = -2x - 2} \ + {x in RR : x = -6} + $ + So the set contains $6$ when $x < 0$. + + And since these inequalities span all $x in RR$, the only members of + the set are ${2, -6}$. +] + +*11c.* + +#proof[ + $ + {x in RR : 2|x+3| + x = 0} + $ + For $x >= -3$, we have + $ + {x in RR : 2(x + 3) + x = 0} \ + = {x in RR : x = -2} \ + = {-2} + $ + For $x < -3$, we have + $ + {x in RR : 2(3 - x) + x = 0} \ + = {x in RR : x = 6 } \ + = {6} + $ + And since these inequalities partition $RR$ the original set is ${-2, 6}$. +] + +*11d.* + +$ + {x in RR : |x| = 6 - |2x|} +$ + +Consider $x >= 0$. Then +$ + {x in RR : x = 6 - 2x} \ + = {x in RR : x = 2} +$ +Consider $x < 0$. Then +$ + {x in RR : -x = 6 + 2x} \ + = {x in RR : x = -2} +$ +So +$ + {x in RR : |x| = 6 - |2x|} = {-2, 2} +$ + +*11e.* + +$ + {x in RR : |x + 3| <= -4x - 2} +$ + +Consider $x >= -3$. Then +$ + {x in RR : x <= -1} \ + = (-infinity, -1] +$ + +Now consider $x < -3$ Then +$ + {x in RR : 3 - x <= -4x - 2} \ + = {x in RR : x <= -5 / 3} \ + = (-infinity, -5 / 3] +$ +But $(-infinity, -5/3) union (-infinity, 1] = (-infinity, 1]$ so that is our +answer. + +*11f.*